2011
DOI: 10.3989/scimar.03373.29a
|View full text |Cite
|
Sign up to set email alerts
|

MtDNA and nuclear data reveal patterns of low genetic differentiation for the isopods <i>Stenosoma lancifer and Stenosoma acuminatum</i>, with low dispersal ability along the northeast Atlantic coast

Abstract: SUMMARY: Evidence for a general lack of genetic differentiation of intertidal invertebrate assemblages in the North Atlantic, based on mtDNA sequence variation, has been interpreted as resulting from recent colonization following the Last Glacial Maximum. In the present study, the phylogeographic patterns of one nuclear and one mtDNA gene fragments of two isopods, Stenosoma lancifer (Miers, 1881) and Stenosoma acuminatum Leach, 1814, from the northeast Atlantic were investigated. These organisms have direct de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Restricted dispersal may indirectly enhance differentiation among populations by promoting the effects of local selection, inbreeding and drift (Pelc et al 2009). However, the high population connectivity found in the same region for other species with direct development (Xavier et al 2012) as well as the existence of a genetic break at Cape Ghir (approximately 250 km south of the southernmost site included in this study, Safi) in a species with larval dispersal (Jaziri and Benazzou 2002), suggest that dispersal ability is probably not the only explanation for the patterns observed in this study. Probably the existence of refugial areas also plays an important role in maintaining this kind of structure.…”
Section: Taxonomic and Ecological Remarksmentioning
confidence: 56%
“…Restricted dispersal may indirectly enhance differentiation among populations by promoting the effects of local selection, inbreeding and drift (Pelc et al 2009). However, the high population connectivity found in the same region for other species with direct development (Xavier et al 2012) as well as the existence of a genetic break at Cape Ghir (approximately 250 km south of the southernmost site included in this study, Safi) in a species with larval dispersal (Jaziri and Benazzou 2002), suggest that dispersal ability is probably not the only explanation for the patterns observed in this study. Probably the existence of refugial areas also plays an important role in maintaining this kind of structure.…”
Section: Taxonomic and Ecological Remarksmentioning
confidence: 56%
“…However, there is increasing evidence that the duration of pelagic stages is not directly correlated with dispersal potential (Johannesson 1988;Strathmann et al 2002). This is supported by the fact that many brooding species have wider geographic distributions showing even more genetic connectivity on large scales than congeners with a planktonic larval stage (Highsmith 1985;Ó Foighil et al 2001;Nunes et al 2011;Hoeksema et al 2012;Xavier et al 2012). Passive dispersal through rafting and floating can greatly enhance natural dispersal in the marine environment and is supposed to be the main process leading to long-distance dispersal of these brooding marine invertebrates (Johannesson 1988;Locke and Corey 1989;Thiel and Gutow 2005b;Goodbody-Gringley et al 2010).…”
Section: Introductionmentioning
confidence: 71%
“…Dispersal by rafting is considered as an important means of maintaining population connectivity on both small and large spatial scales: marine organisms that use rafting for dispersing can maintain large and relatively homogeneous populations with little or no genetic subdivision (Fraser et al 2011;Hoeksema et al 2012;Xavier et al 2012). However, some studies have shown that rafting facilitates dispersal, but does not necessarily maintain genetic connectivity among distant populations (Waters and Roy 2004;Baratti et al 2005;Waters 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such changes have resulted in a latitudinal gradient of genetic divergence, with higher levels of diversity at southern locations, which might have functioned as glacial refugia (Luttikhuizen et al 2008, Kettle et al 2010, Xavier et al 2012. For example, in the eastern Atlantic, the Macaronesian archipelagos, the Iberian Peninsula, and the Atlantic coasts of North Africa have been suggested as such glacial refugia areas (Coyer et al 2004, Maggs et al 2008, Kettle et al 2010.…”
Section: Introductionmentioning
confidence: 99%